The Effect of Student Team Achievement Division (STAD) Cooperative Learning Model on Social Attitudes and Economic Learning Outcomes - Elffani Alpina; Cut Misni Mulasiwi (Jurnal Profesi Keguruan, 2025)
A research gap has been found in Public High School 3 Purwokerto, especially Class XI Social Science, in the form of the use of learning models that still use conventional learning models, which impacts the lack of formation of students’ social attitudes and less than optimal learning outcomes. The aims of this research are 1) To determine the differences in social attitudes and learning outcomes of Class XI Social Science students at Public High School 3 Purwokerto who use the Student Team Achievement Division (STAD) learning model and students who use the conventional learning model; 2) to determine the effect of using the STAD learning model on the social attitudes of students at Public High School 3 Purwokerto, as well as 3) to determine the effect of using the STAD learning model on learning outcomes in economics subjects for students at Public High School 3 Purwokerto. This research is experimental research using quasi-experimental methods. The results of research and data analysis show that 1) there are differences in social attitudes between students who use the STAD learning model and students who use conventional learning methods; 2) there are differences in learning outcomes between students who use the STAD learning model and students who use conventional learning methods; 3) the STAD learning model affects social attitudes; and 4) the STAD learning model affects learning outcomes.